USING LINE WEBTOON IN IMPROVING STUDENTS’ READING COMPREHENSION - Muliany K, Sry Ghina; Baa, Sultan; Radhiyani, Fitri (Universitas Negeri Makassar, 2024)
This research aimed to improve student's reading comprehension of SMKN 6 Makassar by using the Line webtoon application. The research method used was pre-experimental with one experimental group. The population of this research was the XI grade students of SMKN 6 Makassar Culinary Department. The population of this research were the XI grade students of SMKN 6 Makassar Culinary Department. The sample of this research was 33 students of class XI Culinary 2. The experimental group was given a pre-test and post-test to measure students' ability in reading comprehension. The research data was collected by a reading test. The results of this research are significance score for the learning outcome variable is 0.000 <0.05. which means that H0 in this research is rejected and H1 is accepted. It can be concluded there is a significant influence of the use of line webtoon applications in improving students’ reading comprehension.